Information and methodological professionally oriented environment as a factor in self-teaching employees in the period between courses - Глазова, Олександра Павлівна (Educological discourse, 2013)
The paper studies the feasibility of establishing methodology professionally oriented environmental educators, defined its role in the modernization of postgraduate education, considered a function of environment.